Development of Retrievr: A Line-Of-Sight Beacon System for Autonomous Object Return in Indoor Workspaces - Kevin C. Gaza; Baron Terence S. Mijares; Christine Paula C. Rodel; Eliza B. Ayo (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study presents the design, development, and evaluation of Retrierv, a wheeled autonomous device engineered to return loaded objects to their designated locations using Bluetooth Low Energy (BLE) line-of-sight beacon technology. Persistent challenges of object misplacement and spatial disorganization in indoor workspaces motivated this work. Retrierv integrates BLE modules for proximity-based positioning, a Force Sensitive Resistor (FSR) sensor for occupancy detection, and ultrasonic sensors for obstacle avoidance. A descriptive-developmental research design guided by Agile methodology was employed, with iterative prototype development and evaluation across multiple performance dimensions. Testing revealed a mean positional error of 2.72 cm, a maximum load capacity of 11.34 kg (25 lbs), and a mean navigation speed of 0.26 m/s. Quality assurance evaluation demonstrated high usability (System Usability Scale score of 82), strong occupancy detection reliability (98% accuracy), and effective obstacle avoidance (91% detection rate). However, reliability testing showed a Mean Time Between Failures of 42 hours, below the target threshold of 100 hours—an area needing refinement. Retrierv provides a viable and cost-effective solution for automated object repositioning, performing best in controlled indoor environments with hard flooring and moderate obstacle density.